الرقابة الجبائية ودورها في محاربة الغش والتهرب الضريبي - صوالح عمار مريم; تجاني نسيمة; شتيوي محمد الاخضر (جامعة الوادي University of Eloued, 2025)
"هدفت هذه الدراسة إلى قياس مدى فعالية الرقابة الجبائية في محاربة الغش والتهرب الضريبي، من خلال دراسة حالة على مستوى مديرية الضرائب لولاية الوادي. سعت الدراسة إلى التعرف على أنواع وأساليب الرقابة الجبائية المطبقة، ومدى تأثيرها في الحد من الظواهر السلبية التي تمس بمصداقية النظام الضريبي وتؤثر على تحصيل الإيرادات الجبائية. للإجابة على إشكالية البحث، تم اعتماد المنهج الوصفي التحليلي في الجانب النظري، إلى جانب منهج دراسة الحالة في الجانب التطبيقي، حيث استُخدمت أداة المقابلة مع إطارات من مصلحة الرقابة الجبائية، إضافة إلى تحليل بيانات رقمية للفترة (2018–2021). وقد أظهرت نتائج الدراسة أن الرقابة الجبائية تُعد أداة أساسية في الكشف عن التجاوزات الجبائية، وتُساهم في استرجاع حقوق الخزينة العمومية، مما يؤدي إلى تحسين الحصيلة الضريبية. كما تبين أن هناك علاقة واضحة بين تفعيل الرقابة وتراجع مظاهر الغش والتهرب. ومع ذلك، فإن تطبيق الرقابة الجبائية يواجه عدة تحديات، أبرزها ضعف التنسيق بين الإدارات، نقص الموارد البشرية المؤهلة، والوسائل التقنية المحدودة، مما يقلل من فعالية هذه الرقابة في بعض الحالات. "This study aims to assess the effectiveness of tax auditing in combating tax fraud and evasion, through a case study conducted at the Tax Directorate of El Oued Province. The research focuses on identifying the types and mechanisms of tax control applied at the local level, and their impact in reducing practices that undermine the credibility of the tax system and affect revenue collection. To address the research problem, a descriptive-analytical approach was adopted for the theoretical part, while the case study method was used for the practical part. Data was collected through interviews with tax audit officials and analysis of numerical data covering the period from 2018 to 2021. The findings revealed that tax auditing plays a key role in detecting tax violations and recovering public funds, thus improving overall tax revenue. The results also showed a clear relationship between the intensification of auditing efforts and the decline in tax fraud and evasion. However, the study also identified several obstacles hindering the full effectiveness of tax audits, such as limited coordination between administrations, lack of qualified personnel, and insufficient technical tools.
ماستر العلوم المالية والمحاسبية
Keywords: الرقابة الجبائية; الغش الضريبي; التهرب الضريبي; التحصيل الجبائي، مديرية الضرائب; Tax auditing; Tax evasion; Tax fraud; Tax collection; Tax administration